Analisis Potensi Bahaya Alkalinitas dan Salinitas pada Mata Air untuk Kebutuhan Air Irigasi di Kota Batu - Pranantya, Vanadani; Kartikasari, Adelia Nur Isna; Ardiansyah, Ahmad Farid; Kaffa, Niswah Selmi (Jurnal Kridatama Sains dan Teknologi, 2024)
Batu City is an area with abundant water spring potential. Springs are an essential part of the air supply for human domestic needs, industrial activities, and agricultural irrigation activities. Springs in Batu City are mostly used as irrigation water sources, where 15 springs spread across three sub-districts that cover Bumiaji District, Batu District, Junrejo District in Batu City use springs as irrigation water sources. The use of springs as a source of irrigation water, in addition to being considered based on quantity, also needs to be considered for its quality. The quality of water irrigation can be reviewed based on the potential alkalinity hazard (SAR) and potential salinity hazard (EC) values. The values of SAR and EC are explained using the Wilcox Graph. There are 15 springs in Batu City that have EC values in the range of 297.2 µS/cm – 748.3 µS/cm and are classified into Class C2 or moderate salinity hazard potential and SAR in the range of 0.0068 – 0.0294 included in the Class S1 classification or low alkalinity hazard potential. The results of the Wilcox Graph analysis show that the water quality of the 15 springs is in Class C2 – S1 with low alkalinity hazard potential and moderate salinity hazard potential. The results of the Wilcox Graph show that the 15 springs in Batu City that are used as irrigation sources are suitable for use as sources of water irrigation